2020
DOI: 10.1101/2020.10.31.362574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Basis of Stu2 Recruitment to Yeast Kinetochores

Abstract: Accurate chromosome segregation during cell division requires engagement of the kinetochores of sister chromatids with microtubules emanating from opposite poles of the mitotic spindle. In yeast, these bioriented metaphase sister chromatids experience tension as the corresponding microtubules (one per sister chromatid) shorten. Spindle-assembly checkpoint signaling appears to cease from a kinetochore under tension, which also stabilizes kinetochore-microtubule attachment in single-kinetochore experiments in vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…First, we tested whether the basic pair mutant affected chTOG localization to the kinetochore using quantitative fluorescence microscopy and biochemical analysis in nocodazole-treated cells ( Figure 4c , Figure 4—figure supplement 1b,c ). There was no change in localization, consistent with our previous findings in yeast that the C-terminus of Stu2 is necessary and sufficient for stable association with the Ndc80 complex and kinetochores ( Miller et al, 2019 ; Zahm et al, 2020 ). Thus, defects in the regulation of kinetochore-microtubule attachments in cells expressing the basic pair mutant are not due to altered protein localization.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…First, we tested whether the basic pair mutant affected chTOG localization to the kinetochore using quantitative fluorescence microscopy and biochemical analysis in nocodazole-treated cells ( Figure 4c , Figure 4—figure supplement 1b,c ). There was no change in localization, consistent with our previous findings in yeast that the C-terminus of Stu2 is necessary and sufficient for stable association with the Ndc80 complex and kinetochores ( Miller et al, 2019 ; Zahm et al, 2020 ). Thus, defects in the regulation of kinetochore-microtubule attachments in cells expressing the basic pair mutant are not due to altered protein localization.…”
Section: Resultssupporting
confidence: 91%
“…In this experiment, chTOG was still detected on kinetochores, consistent with a kinetochore-bound pool that is separate from microtubule tips ( Figure 1a,b , Figure 1—figure supplement 1a ). chTOG and its budding yeast ortholog, Stu2, physically interact with the Ndc80 kinetochore complex in vitro ( Miller et al, 2016 ; Zahm et al, 2020 ). To test whether they associate in human cells, we immunopurified FLAG-tagged chTOG from HEK-293T cells under conditions refractory to microtubule formation and found that the endogenous Hec1 protein co-purifies ( Figure 1c ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations